Suspected vitamin K-dependent coagulation factor deficiency in pregnancy: A case report - Mariam Ayyash; Meera Chitlur; Johannes Oldenburg; Majid Shaman (Elsevier, 2022)
Hereditary combined vitamin K-dependent clotting factor deficiency (VKCFD) is a rare autosomal recessive congenital bleeding disorder. There are no established guidelines for the care for pregnant women and newborns within the context of VKCFD. A 39-year-old multigravida woman with a family history of VKCFD was referred for high-risk maternal fetal medicine care. Prenatal testing for fetal VKCFD was declined. The patient received vitamin K1 from 36 weeks of gestation and had an uncomplicated vaginal delivery. The baby had normal head ultrasound results, vital signs, and physical examination, with no signs of bleeding: factor levels and coagulation factors were within reference range. Follow-up showed no evidence of VKCFD. A thorough care plan is required for pregnant women whose newborns are at risk for VKCFD.